Differentiated instruction : a guide for world language teachers - Blaz, Deborah (New York, NY : Routledge, 2024)
"In the third edition of a bestseller, author Deborah Blaz helps you differentiate lessons for your world language students based on their learning styles, interests, prior knowledge, and comfort zones. This practical book uses brain-based teaching strategies to help students of all ability levels thrive in a rigorous differentiated learning environment. Each chapter provides classroom-tested activities and tiered lesson plans to help you teach vocabulary, speaking, listening, reading, and writing in world language classes in ways that are interactive, engaging, and effective for all learners. Features new to this edition include: - Activities aligned with the latest ACTFL and CEFR standards - Ideas and activities for project-based learning, virtual learning, and learning with digital tools such as ChatGPT - Up to date with500 latest guidance on learning styles and using variety in teaching - More photocopiable forms, checklists, and handouts for suggested activities You'll also learn how to differentiate assessment effectively to help all students show their full potential. Classroom-ready tools and templates can be downloaded as free Support Material from our website (www.routledge.com/ISBN) for immediate use"--Provided by publisher.
Includes bibliographical references.
Keywords: Individualized instruction; Languages, Modern -- Study and teaching